The effect of Ramadan fasting on sleep quality, total sleep time, and daytime sleepiness in soccer players. - MOUISSA, Amar; SLIMANI, Aissa (Journal of Sport Science Technology and Physical Activities, 2026)
This study aimed to examine the effect of Ramadan fasting on sleep quality, total sleep time, and daytime sleepiness in soccer players. Twenty-four U15 Algerian amateur soccer players voluntarily participated in this descriptive study (age = 14.25 ± 0.60 years, height = 167.08 ± 5.52 cm, weight = 54.34±8.19 kg). The subjects responded to PSQI and ESS scale before (10-days prior), the middle of Ramadan and 21 days after Ramadan, statistical analyses were performed using SPSS. PSQI and ESS scores increased significantly during Ramadan (both p < 0.001), and TST also decreased significantly during Ramadan (p < 0.001), where the ES was large magnitude. Components of the PSQI there were no significant in components 4,5,6 (p ˃ 0.05). Components 1,2,3,7 was significant (p < 0.05). in conclusion Ramadan fasting impaired sleep quality, total sleep time decreased, and increased daytime sleepiness in soccer players.